2017
DOI: 10.1002/isd2.12008
|View full text |Cite
|
Sign up to set email alerts
|

Organisational adoption of telecommuting: Evidence from a developing country

Abstract: Even though telecommuting has been a growing phenomenon in the more advanced world over the past 2 decades, businesses in Africa and more specifically West Africa are yet to adopt the practice, hence providing a gap for research into telecommuting in a developing country such as Ghana to be filled. The study sought to investigate the technological, environmental, and organisational factors that influence telecommuting adoption and to also examine the potential benefits of adopting telecommuting in the operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 44 publications
2
28
0
5
Order By: Relevance
“…Wojcak et al [7] shows that the implementation of this new way to organize work activities brings new challenges for leadership, while Onken-Menke et al [15] present evidence that flexible work schedules, including telework, increase the organization's attractiveness. Managers have to be trained in relation to the ways in which employees that work remotely could be efficiently managed, and new and effective methods to supervise remote workers are required [16].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Wojcak et al [7] shows that the implementation of this new way to organize work activities brings new challenges for leadership, while Onken-Menke et al [15] present evidence that flexible work schedules, including telework, increase the organization's attractiveness. Managers have to be trained in relation to the ways in which employees that work remotely could be efficiently managed, and new and effective methods to supervise remote workers are required [16].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In order to adopt a telecommuting framework, companies have to undergo major cultural change [36]. This requires managers to be properly prepared and trained to manage their team in a bidirectional telecommuting relationship [37]. As telecommuting also means to put trust into the telecommuters by eliminating non-stop visible control [38].…”
Section: Telecommuting and Home Officementioning
confidence: 99%
“…In the pre-Covid 19 period, European countries were reluctant to implement e-working (Beno and Hvorecky, 2021). But e-working has been a growing phenomenon in the advanced world compared to developing countries (Ansong and Boateng, 2018). This is revealed in recent studies, where it is shown that nearly 100 million workers in 35 advanced and emerging countries could be at high risk because they are not able to work remotely.…”
Section: Theoretical Backgroundmentioning
confidence: 99%